Addressable TV Advertising Enhances Advertising Effectiveness - Gumilevskaya, Sofia; Devlin, Joseph; Richardson, Daniel; Diab, Habiba; Liu, Zutao; Casey-Miller, Phoebe (Organizations and Markets in Emerging Economies, 2023)
As TV consumption evolves from traditional linear programming to more on-demand viewing, advertising is also changing, seeking to tailor content to best match the interests of viewers. Addressable advertising is an interactive form of advertising that combines online data personalization with on-demand TV content with the aim of addressing individual viewers and improving advertising outcomes. This study investigated whether audience engagement with advertising (indexed by self-report liking, attention, and memory for an advertisement) was affected by addressability and the screen size on which the content was viewed. Using a limited capacity model of information processing and the elaboration likelihood model as its theoretical bases as well as a physiological measure of attention, we found that people both prefer and remember addressable advertisements more than those that are not relevant to them. In addition, viewing advertisements on large screens improved attention and retention for the content relative to smaller screens.